The Ultimate Test™

Calculus Level 3

Evaluate 1 1 lim y ( arctan ( z = 1 y x 2 x ln ( y z + 1 ) ) + arctan ( 1 z = 1 y x 2 x ln ( y z + 1 ) ) ) d x \int_{-1}^1 \lim_{y \to \infty} \left(\arctan \left(\sum_{z=1}^y x^{2x}\ln (y-z+1)\right) + \arctan \left(\frac 1{\sum_{z=1}^y x^{2x}\ln (y-z+1)} \right) \right) dx

Note: The definition of arctan ( x ) \arctan{(x)} used in this problem is restricted to the range ( π 2 , π 2 ) \left( -\frac { \pi }{ 2 } ,\frac { \pi }{ 2 } \right) .


The answer is 3.14159.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Mar 26, 2019

I = 1 1 lim y ( tan 1 ( z = 1 y x 2 x ln ( y z + 1 ) ) + tan 1 ( 1 z = 1 y x 2 x ln ( y z + 1 ) ) ) d x = 1 1 lim y ( tan 1 ( z = 1 y x 2 x ln ( y z + 1 ) ) + π 2 tan 1 ( z = 1 y x 2 x ln ( y z + 1 ) ) ) d x = 1 1 π 2 d x = π 2 x 1 1 = π 3.142 \begin{aligned} I & = \int_{-1}^1 \lim_{y \to \infty} \left(\tan^{-1} \left(\sum_{z=1}^y x^{2x}\ln (y-z+1)\right) + \color{#3D99F6} \tan^{-1} \left(\frac 1{\sum_{z=1}^y x^{2x}\ln (y-z+1)} \right) \right) dx \\ & = \int_{-1}^1 \lim_{y \to \infty} \left(\tan^{-1} \left(\sum_{z=1}^y x^{2x}\ln (y-z+1)\right) + \color{#3D99F6} \frac \pi 2 - \tan^{-1} \left(\sum_{z=1}^y x^{2x}\ln (y-z+1)\right) \right) dx \\ & = \int_{-1}^1 \frac \pi 2 \ dx = \frac \pi 2 x \ \bigg|_{-1}^1 = \pi \approx \boxed{3.142} \end{aligned}

Peter Macgregor
Mar 27, 2019

From easy trigonometry in a right angled triangle you can see that

a r c t a n ( a ) + a r c t a n ( 1 a ) = π 2 arctan(a)+arctan\left(\frac{1}{a}\right)=\frac{\pi}{2}

The y limit is seen to be irrelevant and the integral then simplifies to

1 1 π 2 d x = π \int_{-1}^{1}\frac{\pi}{2}dx=\boxed{\pi}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...